Black Power in the Boardroom: Corporate America, the Sullivan Principles, and the Anti-Apartheid Struggle. (March 2020) - LEVY, JESSICA ANN
Abstract : This article traces the history of General Motors' first black director, Leon Sullivan, and his involvement with the Sullivan Principles, a corporate code of conduct for U.S. companies doing business in Apartheid South Africa. Building on and furthering the postwar civil rights and anti-colonial struggles, the international anti-apartheid movement brought together students, union workers, and religious leaders in an effort to draw attention to the horrors of Apartheid in South Africa. Whereas many left-leaning activists advocated sanctions and divestment, others, Sullivan among them, helped lead the way in drafting an alternative strategy for American business, one focused on corporate-sponsored black empowerment. Moving beyond both narrow criticisms of Sullivan as a "sellout" and corporate propaganda touting the benefits of the Sullivan Principles, this work draws on corporate and "movement" records to reveal the complex negotiations between white and black executives as they worked to situate themselves in relation to anti-racist movements in the Unites States and South Africa. In doing so, it furthermore reveals the links between modern corporate social responsibility and the fight for Black Power within the corporation.